The Influence of Store Atmosphere and Product Price on Impulse Buying at Offline Store - Dewanti, Meisita Nabilla; Nirawati, Lia (Almana : Jurnal Manajemen dan Bisnis, 2023)
Currently, many business people take advantage of technology by selling their products online to minimize the costs incurred for doing business through the marketplace. However, this does not reduce and affect the growth of the retail or offline store business. Thus, retail stores must build a good store atmosphere at affordable prices so that consumers make impulse purchases. This study aims to analyze the effect of store atmosphere and product prices on impulse buying at the Miniso offline store in Tunjungan Plaza Surabaya. This study uses a quantitative approach and uses multiple linear regression analysis techniques. The population in this study were Miniso consumers at Tunjungan Plaza Surabaya. The sampling technique used is a non-probability side with a purposive sampling type. Data collection through questionnaires was distributed to 100 respondents. The data were processed using SPSS 29. The conclusion from the results of this study showed that a partially stored atmosphere did not affect impulsive purchases (0,547 > 1,984 and a significance of 0,586 > 0,05). However, product prices have a partial effect on impulsive purchases (2,803 > 1,984 and 0,006 significantly<0.05). Simultaneously, store atmosphere and product prices affect impulse buying (8,073 > 3,090 and a significance of 0,001 <0,05).